2017
DOI: 10.1088/1361-648x/aa63c6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the time-resolved magneto-optical Kerr effect for ultrafast magnetization dynamics in ferromagnetic thin films

Abstract: We discuss fundamental aspects of laser-induced ultrafast demagnetization probed by the time-resolved magneto-optical Kerr effect (MOKE). Studying thin Fe films on MgO substrate in the absence of electronic transport, we demonstrate how to disentangle pump-induced variations of magnetization and magneto-optical coefficients. We provide a mathematical formalism for retrieving genuine laser-induced magnetization dynamics and discuss its applicability in real experimental situations. We further stress the importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 45 publications
5
47
0
Order By: Relevance
“…High optical reflectance ensures the absence of excited carriers in Au providing much larger Δf than in the thermal case. Excited into the sp band of Fe [14,24] Fig. 1(c)].…”
mentioning
confidence: 99%
“…High optical reflectance ensures the absence of excited carriers in Au providing much larger Δf than in the thermal case. Excited into the sp band of Fe [14,24] Fig. 1(c)].…”
mentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ mechanisms involved with Elliot-Yafet scattering 10,[41][42][43] and spin current 6,7,11,44 have been discussed. Very recently, a quantitative study and comparison between fluence-dependent experiments and a model that includes non-equilibrium effects microscopically has been reported 45 . This investigation revealed that the non-thermal electron contribution could be another critical mechanism in understanding ultrafast photoinduced spin dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The precession amplitudes are obtained from the absolute values of the KR angle in the transient KR signals 12 . The field-independent small amplitude background, which is due to the response of the electron system and not related to the magnetization 21 , has been subtracted from the experimental values. At W = 100 mW the precession amplitude reaches 0.1% of the saturation magnetization M 0 .…”
Section: Discussionmentioning
confidence: 99%